By Mouse & Frog [videorecording (DVD)] - Freedman, Deborah (Deborah Jane), 1960-; Berneis, Susie (Dreamscape Media, LLC, 2015)
Fastidious Mouse has one idea about how to tell a story. Free-spirited Frog has another. What happens when Frog crashes into Mouse's story with some wild ideas? Chaos! Followed by the discovery that working together means being willing to compromise - and that listening to one another can lead to the most beautiful stories of all.